HANDLING SYSTEMS ENTERTAINMENT ENTERTAINMENT AND TAX REVENUE SERVICE ROUTINE IN REGIONAL DKI JAKARTA - Rudi Hari Kristianto; Ir. Irwan Nirmara, MMSI (Jurnal Sistem Informasi, 1996)
At the present time-intensive government is actively implementing development to further improve living standards and all aspects of life of the nation to achieve the goal of independence that is fair and prosperous society based on Pancasila, it is necessary to support the cost of which is large enough to support the smooth and success of the implementation of the basic tasks and achieve goals.